(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
The results of Kramers- Kronig analysis of all the reflectivity spectra were reported based on the results of interband optical transitions observed by means of reflectivity measurements of Hg1-xFexS (x=0.01, 0.04 and 0.06) crystals in the energy range 1.5–12eV. We used a computer program for Kramers-Kronig analysis to determine the eRe and eIm spectra. The observed dependence of the positions of the spectral peaks on the Fe content allows us to estimate the contribution of Fe-derived states to the band structure of b‑HgS semiconductor. The interpretation of structures spectra as a result of interband transitions between occupied valence bands and the empty conduction bands are presented along with some conclusions concerning the electronic band structure of -HgS. عرضت نتائج تحليل كرامرز– كرونيغ لجميع أطياف الانعكاسية، اعتماداً على نتائج الانتقالات الضوئية ما بين العصابات بوساطة قياسات الانعكاسية للبلوراتHg1-xFexS (x=0.01, 0.04, 0.06) في مجال الطاقة من 1.5 إلى 12 eV. استخدمنا برنامج حاسوبي لتحليل كرامرز-كرونيغ لتحديد الأطياف Re و Im. تبين أن علاقة مواقع القمم الطيفية الملاحظة بتركيز الحديد تسمح لنا بتقدير مشاركة سويات الحديد في البنية العصابية لنصف الناقل b‑HgS. فسرت بنى الأطياف كنتيجة للانتقالات الداخلية ما بين عصابات التكافؤ المملوءة وعصابات الناقلية الفارغة، وقد أوضحنا استنتاجاتنا الخاصة بالبنية الإلكترونية للبلورة b‑HgS.